PENGARUH PERSEPSI KEMUDAHAN SISTEM DAN PERSEPSI KENYAMANAN TERHADAP SIKAP POSISTIF NASABAH BANK BNI CABANG ENDE DALAM MENGGUNAKAN LAYANAN MOBILE - Soo, Maria Yulita Arima; Marselina, Apriana; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2020)
This study aims to determine: (1) the effect of perceptions of the ease of the system on the positive attitude of customers in using mobile banking BNI Ende Branch Bank. (2) the effect of perceived comfort on the positive attitude of customers in using BNI BNI Bank Ende mobile banking. (3) the effect of perceived ease of system and perceived comfort together on the positive attitude of customers in using BNI BNI Bank Ende Branch mobile banking. The population in this study are customers of Bank BNI Ende Branch who use mobile banking or at least know information about the service. The sample selection uses a purposive sampling method. The number of research samples were 90 respondents of Bank BNI Branch Ende. The method used is a quantitative research method. This study uses primary data, questionnaires and secondary data, articles and journals. In this study using descriptive statistics, data quality tests, classic assumption tests, multiple regression analysis, and hypothesis testing and analyzed using the SPSS 24 application. The results showed that the effect of perceived ease of system significantly influenced customers 'positive attitudes in using mobile banking, perceived comfort significantly influenced customers' positive attitudes in using mobile banking, perceived ease of system and perceived convenience both influenced customer positive attitudes in using mobile banking.